Nowhere better than here eaudiobook - Guillory, Sarah (Blackstone Publishing, 2022)
In a town slowly being destroyed by rising tides, one girl must fight to find a way to keep her community's spirit from drowning. For thirteen-year-old Jillian Robichaux, three things are sacred: bayou sunsets, her grandmother Nonnie's stories, and the coastal Louisiana town of Boutin that she calls home. When the worst flood in a century hits, Jillian and the rest of her community band together as they always do―but this time the damage may simply be too great. After the local school is padlocked and the bridges into town condemned, Jillian has no choice but to face the reality that she may be losing the only home she's ever had. But even when all hope seems lost, Jillian is determined to find a way to keep Boutin and its indomitable spirit alive. With the help of friends new and old, a loveable golden retriever, and Nonnie's storytelling wisdom, Jillian does just that in this timely and heartfelt story of family, survival, and hope. In her stunning debut middle grade novel, Sarah Guillory has written a lush story about an indomitable girl fighting against the effects of climate change.